Molecular Van Der Waals Heterojunction Photodiodes Enabling Dipole‐Induced Polarity Switching. Issue 10 (2nd September 2022) - Shin, Jaeho; Yang, Seunghoon; Eo, Jung Sun; Jeon, Takgyeong; Lee, Jaeho; Lee, Chul‐Ho; Wang, Gunuk
Abstract: Solid‐state devices capable of controlling light‐responsive charge transport at the molecular scale are essential for developing molecular optoelectronic technology. Here, a solid‐state molecular photodiode device constructed by forming van der Waals (vdW) heterojunctions between standard molecular self‐assembled monolayers and two‐dimensional semiconductors such as WSe2 is reported. In particular, two non‐functionalized molecular species used herein (i.e., tridecafluoro‐1‐octanethiol and 1‐octanethiol) enable bidirectional modulation of the interface band alignment with WSe2, depending on their dipole orientations. This dipole‐induced band modulation at the vdW heterointerface leads to the opposite change of both photoswitching polarity and rectifying characteristics. Furthermore, compared with other molecular or 2D photodiodes at a similar scale, these heterojunction devices exhibit significantly enhanced photo‐responsive performances in terms of photocurrent magnitude, open‐circuit potential, and switching speed. This study proposes a novel concept of the solid‐state molecular optoelectronic device with controlled functions and enhanced performances. Abstract : A molecular‐scale photodiode with WSe2 with a high ON–OFF ratio, fast response time, and polarity switching enabled by interfacial band engineering is developed. Furthermore, compared with other molecular or 2D photodiodes at a similar scale, the devices exhibit significantly enhanced photo‐responsive performances. This study proposes a novel concept of the solid‐state molecular optoelectronic device with controlled functions and enhanced performances.